Development and Initial Validation Steps of a Standardized Video Test Assessing Professional Vision of Classroom Management and Instructional Support - Jasmin Lilian Bauersfeld; Patricia Bourcevet; Heike Hahn; Bernadette Gold (Education Sciences)
Teachers’ professional vision (PV) is important for implementing teaching quality in classrooms. PV entails noticing and reasoning on relevant events out of classrooms’ complexity. Many events entail situations of classroom management and instructional support, which are crucial for student learning. Standardized video-based instruments have been used to validly and reliably gmeasure PV of classroom management and PV of instructional support. However, most instruments focused on one teaching quality dimension (e.g., on classroom management or instructional support) and used several classroom videos for each focus. Therefore, the present study gives preliminary insights into the standardized assessment of PV of multiple foci of teaching quality (i.e., classroom management and instructional support) using a single classroom video from an elementary math lesson. Participants were 221 math master’s student teachers, 83 math bachelor’s student teachers, 40 math pre-service teachers in the induction program, 19 elementary math teachers, and 19 math students. The results of confirmatory factor analyses displayed a good fit for a two-dimensional structure with the following factors: PV of classroom management and PV of instructional support. Furthermore, our findings showed that master’s student teachers and pre-service teachers differed from bachelor’s student teachers and math students in PV of classroom management, but not when compared to experienced teachers. In conclusion, the findings mark an important first step in developing an instrument that captures classrooms’ complexity by simultaneously measuring PV of multiple foci of teaching quality using the identical classroom video.